Understanding mental health promotion in organized leisure communities for young people: a realist review - Kusier, Amalie Oxholm; Ubbesen, Thilde Risager; Folker, Anna Paldam (Frontiers in Public Health, 2024)
Introduction A large proportion of young people reports poor mental health, which is a major public health concern. Positive mental health is important for young people's development, quality of life, functioning in everyday life, and long-term possibilities. Thus, there is a great need to develop and implement mental health-promoting initiatives and activities in young people's lives. Participating in organized leisure communities has a positive impact on mental health and wellbeing. However, more knowledge is still needed about why and how participating in organized leisure communities targeting young people can promote mental health. The aim of this study was to gain knowledge about the mental health-promoting potential of organized leisure communities for young people by exploring the active ingredients that contribute to mental health promotion. Method Given the complexity of the subject, this study implemented a realist review approach to explore the interaction between context, mechanism, and outcome. The study follows Pawsons' five key steps for conducting a realist review: (1) clarify scope, (2) search for evidence, (3) study selection criteria, and procedures, (4) data extraction, and (5) data synthesis and analysis. The literature was systematically searched in the four databases PsycINFO, Scopus, Embase, and SocIndex. Results In the literature search, a total of 11,249 studies were identified, of which 52 studies met the inclusion criteria. Based on the 52 studies, seven different contexts i.e., types of organized leisure communities for young peoples were identified. Across the seven different types of organized leisure communities, five active ingredients that promoted the mental health of young people were identified: social connectedness, development of skills, development of self-confidence, pleasure-driven participation, and safety and trust. Conclusion This review contributes important knowledge about how to promote young people's mental health when participating in organized leisure communities. Moving forward, an important task consists of establishing and maintaining the five active ingredients in organized leisure communities through e.g., education and training that strengthens the skills and knowledge of those responsible for facilitating the leisure communities, such as sports coaches or music teachers, as these adults play a central role in supporting the active ingredients.